Family income, maternal psychological distress and child socio-emotional behaviour: Longitudinal findings from the UK Millennium Cohort Study - Katharine Noonan; Richéal Burns; Mara Violato (Elsevier, 2018)
The association between low family income and socio-emotional behaviour problems in early childhood has been well-documented, and maternal psychological distress is highlighted as central in mediating this relationship. However, whether this relationship holds for older children, and the precise mechanisms by which income may influence child behaviour is unclear.This study investigated the relationship between family income and child socio-emotional behaviour at 11 years of age, and examined the mediating role of maternal psychological distress over time using the UK Millennium Cohort Study.The primary outcome was parent-reported behavioural problems, as captured by the Total Difficulties Score (TDS), derived from the Strengths and Difficulties Questionnaire (SDQ). Secondary outcomes were the emotional, peer-related, conduct, and hyperactivity/inattention problems subscales of the SDQ; and teacher-reported TDS. Permanent family income was the primary exposure variable; frequency of poverty up to age 11 years was the secondary exposure variable. Maternal psychological distress was operationalised to reflect the trajectory from child birth to age 11. Multivariable logistic regression models were used to estimate the effect of permanent family income on child behaviour at age 11, controlling for maternal psychological distress and other relevant covariates.Results showed a statistically significant protective effect of increased permanent family income on the likelihood of behavioural problems at age 11. This finding was consistent for all SDQ subscales apart from emotional problems, and was strongest for teacher-reported behavioural problems. Maternal distress was an important mediator in the income-child behaviour relationship for parent-reported, but not teacher-reported, behavioural problems.The results of this study strengthen empirical evidence that the child behaviour-income gradient is maintained in older childhood. Mother's psychological distress, particularly longstanding or recurrent, appears to contribute to this relationship. These findings may validate calls for psychosocial and financial supports for families affected by parental mental health issues. Keywords: UK, Child health and development, Income gradient, Maternal psychological distress, Health inequalities